PENGARUH PENERIMAAN PAJAK KENDARAAN BERMOTOR (PKB) DAN BEA BALIK NAMA KENDARAAN BRMOTOR (BBNKB) TERHADAP PENDAPATAN ASLI DAERAH (PAD) PROVINSI SUMATERA BARAT - Rita Putri Wulandari; Rita Dwi Putri; Lili Wahyuni (Bajang Institute, 2022)
This study aims to determine the effect of Motor Vehicle Tax and Motor Vehicle Transfer Fee on Regional Original Income in West Sumatra Province in 2012 - 2021. The type of data used is secondary data in the form of realization of motor vehicle tax receipts, transfer fees for motorized vehicles and regional original income for the period 2012 - 2021. The sample in this study uses total sampling. The analysis used includes normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, hypothesis testing, and coefficient of determination R square. The results of this study indicate that (1) Motor Vehicle Tax has an effect on Regional Original Income. This is evidenced by the value of t arithmetic 10,066 > t table 1,895 while for significance 0,000 < 0,05. (2) The Transfer Fee for Motor Vehicles does not affect the Regional Original Revenue. This is evidenced by the value of t arithmetic 1,329 < t table 1,895, while for significance 0,220 > 0,05. (3) Motorized Vehicle Tax and Motor Vehicle Transfer Fees simultaneously affect Regional Original Income. This is evidenced by the calculated F value 50,745 > F table 4,737 with a significance of 0,000 < 0,05.